Effect of exogenous GXC (xylanase, β-glueanase and cellulase) on digestion of paddy-based diets in growing pigs - XU Zi-rong; LU Jian-jun (浙江大学学报. 农业与生命科学版, 2001)
Nighty Landrace X Jia growing pigs. (35±0.40) kg, were used to investigate the effects of exogenous GXC (xylanase, β-glucanase and cellulase) on the digestion of paddy-based diets and approach to the mechanism. The results of feeding trial showed that GXC supplementation significantly increased ADG by 8.78% (P<0.05) and decreased F/G by 9.42% (P<0.05). Adding GXC significantly improved apparent digestibility of CP. EE and CF by 18.76% (P<0.01).16.04% (P<0.05) and 108.57% (P<0.05) respectively. Both did not show significant differences compared with cornbased group. Addition of GXC had no effect on the activities of the enzymes in the pancreas and the pepsin in the gastric mucosa. The activities of proteolytic enzyme and α-amylase in duodenal contents were increased by 99.07% (P<0.01) and 18.41% (P<0.05) with the addition of GXC.